2006
DOI: 10.1016/j.ydbio.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Distinct signals from the microbiota promote different aspects of zebrafish gut differentiation

Abstract: All animals exist in intimate associations with microorganisms that play important roles in the hosts' normal development and tissue physiology. In vertebrates, the most populous and complex community of microbes resides in the digestive tract. Here, we describe the establishment of the gut microbiota and its role in digestive tract differentiation in the zebrafish model vertebrate, Danio rerio. We find that in the absence of the microbiota, the gut epithelium is arrested in aspects of its differentiation, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
541
3
11

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 546 publications
(567 citation statements)
references
References 59 publications
12
541
3
11
Order By: Relevance
“…is known to be a major constituent of the gut microbiota and mono-association experiments with this bacterium showed that it increases the expression of digestive enzymes and abundance of secretory cells in the gut epithelium. Its presence furthermore enabled the uptake of protein macromolecules and influenced gut motility (Bates et al, 2006). Interestingly, Gorokhova et al (2015) found a strong decrease in feeding activity, digestion efficiency and carbon uptake in Daphnia of which the gut microbiota was affected by antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…is known to be a major constituent of the gut microbiota and mono-association experiments with this bacterium showed that it increases the expression of digestive enzymes and abundance of secretory cells in the gut epithelium. Its presence furthermore enabled the uptake of protein macromolecules and influenced gut motility (Bates et al, 2006). Interestingly, Gorokhova et al (2015) found a strong decrease in feeding activity, digestion efficiency and carbon uptake in Daphnia of which the gut microbiota was affected by antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although D. magna has digestive enzymes used for breaking down food such as proteases, amylases and lipases (Hasler, 1935;von Elert et al, 2004), the contribution of gut microbiota to these functions is unknown. It also remains to be seen whether bacteria affect the development and maturation of the Daphnia gut, as they do in the development of vertebrate gut epithelia (Hooper, 2004;Rawls et al, 2004;Bates et al, 2006), or whether bacteria promote growth factor signaling and intestinal stem cell activity as in Drosophila (Shin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although some microbes are parasites that can cause disease, many others lie on the spectrum between commensalism and mutualism and may significantly influence their hosts' nutrition (Dethlefsen et al, 2007), development (Bates et al, 2006) and disease resistance (Macpherson and Harris, 2004;Koch and Schmid-Hempel, 2011). The use of model organisms such as the fruit fly Drosophila melanogaster, the nematode Caenorhabditis elegans, the house mouse Mus musculus and the zebrafish Danio rerio has facilitated understanding of the mechanisms by which certain biological functions of the hosts are modulated by their microbiota (Rawls et al, 2004;Turnbaugh et al, 2006;Cabreiro and Gems 2013;Erkosar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The microorganisms that reside on and inside humans and other vertebrate animals are remarkable, not only because of their importance to host health and development (Bates et al, 2006;Fraune and Bosch, 2010;Sommer and Bäckhed, 2013), but also because they assemble into complex communities de novo in every new hatchling or infant host. The processes responsible for structuring these complex systems, often referred to as a host's microbiota, are not well understood despite a strong interest in manipulating them to improve human health.…”
Section: Introductionmentioning
confidence: 99%